Broadband Sound Administration Improves Sleep Onset Latency in Healthy Subjects in a Model of Transient Insomnia - Messineo, Ludovico; Taranto-Montemurro, Luigi; Sands, Scott A.; Oliveira Marques, Melania D.; Azabarzin, Ali; Wellman, David Andrew (Frontiers in Neurology, 2017)
Background: Insomnia is a major public health problem in western countries. Previous small pilot studies showed that the administration of constant white noise can improve sleep quality, increase acoustic arousal threshold, and reduce sleep onset latency. In this randomized controlled trial, we tested the effect of surrounding broadband sound administration on sleep onset latency, sleep architecture and subjective sleep quality in healthy subjects. Methods: Eighteen healthy subjects were studied with two overnight sleep studies approximately one week apart. They were exposed in random order to normal environmental noise (40.1 [1.3] dB) or to broadband sound administration uniformly distributed in the room by two speakers (46.0 [0.9] dB). To model transient insomnia, subjects went to bed (“lights out”) 90 min before usual bedtime. Results: Broadband sound administration reduced sleep onset latency to stage 2 sleep (time from lights out to first epoch of non-REM-sleep stage 2 (19[16] vs 13[23] mins, p=0.011; median reduction 38% baseline). In a subgroup reporting trouble initiating sleep at home (Pittsburgh Sleep Quality Index section 2 score ≥1), sound administration improved subjective sleep quality (p=0.037) and the frequency of arousals from sleep (p=0.03). Conclusions: In an experimental model of transient insomnia, broadband sound administration significantly reduced sleep onset latency by 38% compared to normal environmental noise. These findings suggest that broadband sound administration might be helpful to minimize insomnia symptoms in selected individuals.